3-D Characterisation of Nonwoven Fabrics by means of an optical system - Pereira, Mário José Teixeira (2010)
The characterisation of fabric structure by means of quantified parameters is essential for the control of the fabrication processes and the resulting properties of the nonwoven materials. Important parameters of the structure are the porosity, the mean pore size and the pore size distribution, the specific area of the texture, the fibres orientation the last one needing to be characterised in the three dimension of the fabric web. In this research work we intend to evaluate the porous fibres orientation in geotextiles nonwovens using a procedure based on the fibres light conducting and their associated scattering. The interpretation of the phenomena is made through a modelisation concept of the pore fibre interfaces